Numerical comparison of blast waves generated by cylindrical explosive charges with varying shapes and materials - Panowicz, Robert; Trypolin, Michał; Konarzewski, Marcin (Computer Assisted Methods in Engineering and Science, 2017)
A significant influence of explosive charge geometry is frequently observed during experimental testing. In this paper, the effect of explosive charge shape, along with its material properties, on the generated blast waves is studied. The FEM analysis was conducted for six different explosive materials and three different cylindrical shapes, with geometrical proportions of length L to diameter D varying between 2, 1 and 0.25 and constant charge mass. We found that the blast wave generated by detonation is susceptible to shape changes. However, the different explosive materials were influenced by the charge shape in almost the same way, with only insignificant differences resulting from the material properties.